2019
DOI: 10.26832/24566632.2019.0404015
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyofaunal diversity of Basurabad Beel in regards with threat factors and conservation measures, Bangladesh

Abstract: The present study was conducted to assess the temporal distribution of ichthyofaunal composition of Basurabad beel in Khulna, Bangladesh and investigated the fish biodiversity and core threats to biodiversity to provide recommendations for conservation in the beel. During the study period, total 33 fish species were recorded belonging to 6 orders. The order wise fish species availability was maximum in Perciformes (39.40%) and minimum in Beloniformis (3%). The value of Shannon-Weaver diversity index was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In contrast to the current study, Chakraborty et al, (2021) listed a total of 91 species from 65 genera that were found in the Charia beel. Compared to the current study, Rahman et al, (2019) only counted 33 fish species from 6 orders in the Basurabad beel. According to Siddique et al, (2013), 58 fish species from 21 families and 9 orders were found in the dogger beel.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast to the current study, Chakraborty et al, (2021) listed a total of 91 species from 65 genera that were found in the Charia beel. Compared to the current study, Rahman et al, (2019) only counted 33 fish species from 6 orders in the Basurabad beel. According to Siddique et al, (2013), 58 fish species from 21 families and 9 orders were found in the dogger beel.…”
Section: Resultsmentioning
confidence: 73%
“…A "beel" is a low-lying depression that resembles a lake in a wetland or floodplain, which is regarded as one of the preferred natural habitats for Bangladesh's indigenous fish species and contribute 2.3% of the nation's annual fish production. These permanent wetlands, covering an area of around 114,161 ha (DoF 2022, Pandit et al, 2021) are used by indigenous fish as a natural habitat for food and shelter (Rahman et al, 2019). Beels plays an important role in inland fish production and fishermen's livelihoods, while fish stocks fully or partially support fishermen's livelihoods (Islam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh produced 4.6 million metric tons of fish overall in the 2020-2021 fiscal year, ranking third (3 rd ) in the world for open-water fish production and fifth (5 th ) for culture fish output [7]. The lives of more than 12 million fishermen in Bangladesh are being steadily threatened by the ongoing fall in fish catches despite the country's possession of extraordinarily fertile inland waterways covering around 45,000 km 2 [8][9][10]. As opposed to several other rivers in the coastal region, the Sandha river is one of the significant fish reservoirs in Bangladesh's southern coastal area [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a means of livelihood, more than 11% of Bangladesh's entire population is employed in this sector, both full-time and part-time ( DoF, 2018 ). Overexploitation, siltation, industrial pollution, use of synthetic monofilament nets, overdosing of fertilizers and insecticides in agricultural lands, and ecological disturbances are all contributing to a decline in fish output ( Hossain et al., 2012 ; Rahman et al., 2019a , Rahman et al., 2019b ). Changing land use, modifying river flow regimes, riparian and physical habitat loss, water pollution, alien species invasions, and heavy exploitation of fish stocks are only a few of the anthropogenic disturbances that have a significant impact on riverine ecosystems and fisheries ( Arthington et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%